Callipeltosides A, B and C: Total Syntheses and Structural Confirmation. Issue 38 (31st July 2015) - Frost, James R.; Pearson, Colin M.; Snaddon, Thomas N.; Booth, Richard A.; Turner, Richard M.; Gold, Johan; Shaw, David M.; Gaunt, Matthew J.; Ley, Steven V.
Abstract Since their isolation almost 20 years ago, the callipeltosides have been of long standing interest to the synthetic community owing to their unique structural features and inherent biological activity. Herein we present our full research effort that has led to the synthesis of these molecules. Key aspects of our final strategy include 1) synthesis of the C1–C9 pyran core (5) using an AuCl3‐catalysed cyclisation; 2) formation of C10–C22 vinyl iodide (55) by sequential bidirectional Stille reactions and 3) diastereoselective union of these advanced fragments by means of an alkenylzinc addition (d.r.=91:9 at C9). The common callipeltoside aglycon (4) was completed in a further five steps. Following this, all three sugar fragments were appended to provide the entire callipeltoside family. In addition to this, D‐configured callipeltose B was synthesised and appended to the callipeltoside aglycon. The 1H NMR spectrum of this molecule was found to be significantly different to the natural isolate, further supporting our assignment of callipeltoside B (2).